2023
DOI: 10.3390/fishes8060298
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nanocurcumin Impacts Blood Biochemical Parameters and Works Synergistically with Florfenicol in African Catfish Challenged with Aeromonas veronii

Abstract: The present study investigated the effects of dietary supplementation of nanocurcumin (NCur = 150 ppm) in African catfish feed for 15 days along with two doses of florfenicol—a therapeutic dose (FFC1 = 10 mg/kg.BW) and a high dose (FFC2 = 30 mg/kg.BW). Serum biochemical parameters and histopathological changes in liver and kidney tissues were determined post-feeding. Additionally, fish were experimentally challenged with a virulent strain of Aeromonas veronii to explore the fish’s capacity to resist infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Dietary inclusion of CURNPs (100 or 150 mg/kg) enhanced growth indices (FBW, WG%, DWG, RGR) and improved feed utilization of D. labrax. The obtained results coincided with studies reporting the positive effects of CURNPs on the growth metrics and feed utilization in O. niloticus (Eissa et al, 2022;Elabd et al, 2023), C. carpio (Abdel-Tawwab & Abbass, 2017Pirani et al, 2021), and African catfish (Clarias gariepinus) challenged with Aeromonas veronii (Mansour et al, 2023). The group of D. labrax that received the high dose of CURNPs exhibited a greater growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Dietary inclusion of CURNPs (100 or 150 mg/kg) enhanced growth indices (FBW, WG%, DWG, RGR) and improved feed utilization of D. labrax. The obtained results coincided with studies reporting the positive effects of CURNPs on the growth metrics and feed utilization in O. niloticus (Eissa et al, 2022;Elabd et al, 2023), C. carpio (Abdel-Tawwab & Abbass, 2017Pirani et al, 2021), and African catfish (Clarias gariepinus) challenged with Aeromonas veronii (Mansour et al, 2023). The group of D. labrax that received the high dose of CURNPs exhibited a greater growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 87%
“…However, many studies have revealed that CURNPs can decrease the hepatic enzymes in various fish species after feeding trial (Eissa et al, 2023;Eissa et al, 2022), an effect that wasn't observed in our study. Given the normal organ function parameters reported in this study, it could be concluded that CURNPs were safe in D. labrax and that the hepatoprotective role of CUR and its nano form could be observed when the fish is challenged with pathogenic microbes, such as Aspergillus flavus (Eissa et al, 2023;Eissa et al, 2022), Streptococcus agalactiae (Alhawas et al, 2023) and Aeromonas veronii (Mansour et al, 2023).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation